How “Rational” Is Urban Public Corruption? - Cameron Elliott Gordon (Urban Science)
This article reviews the literature on both (a) the general theory of public corruption and its evolution over time; and (b) the history of urban public corruption during the modern period into the present. In addition, this article conducts a historical narrative form of representation to structure the historical facts, synthesizing chronologically disparate elements into a synchronic unity, with the focus of the narrative on “urban public corruption”, both empirically (i.e., how its manifestation changed over time in particular times and places) and conceptually (i.e., how the ideas about these manifestations altered with the passage of time). The period considered is mainly from the onset of the Industrial Revolution in the mid-18th century, up to the present time, with a major focus on contemporary developments. This review illustrates that the extraction of rents has always been a key feature of urban corruption. Nonetheless, not all extraction is alike institutionally and historically. The analysis presented here indicates that the modern notion of corruptions has been the product of a long evolution which, no doubt, is not over. The present idea is of corruption as a technocratic one of a “coherent, discrete referent” based on rational choice theory, which can be applied to define acts as corrupt regardless of social context. This is found to be not applicable in all times and places. Defining what constitutes a “corrupt” act varies considerably across cultures, across times, between nations and cities, and sometimes even within them. This article closes with a template about possible behavioral spheres of urban corruption, incorporating overlaps and gaps between “rational”, “maximizing”, and “atomistic” motivations. The conclusion is that the current consensual “rational choice” understandings only apply to those acts which incorporate all three aspects, with variants drawn from “behavioral” economics expanding applicability somewhat, but still leaving out a great deal of city corruption on the ground which is much more social and institutional than present understandings allow for.